Tasks for language teachers : - Parrott, Martin (Cambridge University Press, 1993)
This practical resource for teacher trainers and teachers of English and other languages provides task material for training seminars and development groups. The topics are wide-ranging - from the nature and processes of language learning to specific materials and techniques for use by teachers. The tasks are designed to stimulate meaningful discussion of issues related to language teaching and learning. It contains 40 tasks, of two types. The 'Discussion Tasks' are designed to allow users to examine general principles and issues in the context of their specific teaching circumstances, and to exchange ideas. The 'Classroom-based Tasks' provide users with a practical framework for small-scale classroom research - testing out ideas, assumptions and hypotheses in the context of their own classes and learners. In course situations where it is not possible for each participant to have a copy, the trainer may photocopy relevant pages for use by the participants.